1999
DOI: 10.1111/j.1745-459x.1999.tb00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fermentation and Storage Conditions on the Sensory Properties of Plain Low Fat Stirred Yogurts

Abstract: Influence of strain association, temperature, pH and storage on the sensory properties of low fat stirred yogurt was studied through a factorial design including three associations of thermophilic lactic acid bacteria (one Lactobacillus delbrueckii subsp. bulgaricus, one ropy and one nonropy Streptococcus thermophilus strains), three incubation temperatures (39C, 42C and 45C), two final fermentation pH (4.4 and 4.8) and two storage times (7 and 21 days). The 36 formulated yogurts were assessed by Quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 24 publications
7
28
1
4
Order By: Relevance
“…Finally, the highest values of pH and less lactic acidity obtained with St-Lr and St-Bl with respect to the other two co-cultures are consistent with the heterolactic nature of both Lr (Jyoti et al, 2003) and Bl (Bongaerts et al, 2005), and the lower pH after D7 with St-Lb compared with StLr to the formation of acetic acid instead of ethanol (Bongaerts et al, 2005). The values of pH after D1 are not so far from those reported by Moreira et al (2000) (3.76-4.39), who analyzed samples of milk fermented by different strains of L. bulgaricus and S. thermophilus, and by Martin et al (1999) after 30-day storage at 5°C (4.18-4.36). Besides, Damin et al (2006) detected an average lactic acidity in commercial yoghurts (10.1 mg g À1 ) practically coincident to the average value of this work after D7.…”
Section: Post-acidification and Aciditysupporting
confidence: 89%
“…Finally, the highest values of pH and less lactic acidity obtained with St-Lr and St-Bl with respect to the other two co-cultures are consistent with the heterolactic nature of both Lr (Jyoti et al, 2003) and Bl (Bongaerts et al, 2005), and the lower pH after D7 with St-Lb compared with StLr to the formation of acetic acid instead of ethanol (Bongaerts et al, 2005). The values of pH after D1 are not so far from those reported by Moreira et al (2000) (3.76-4.39), who analyzed samples of milk fermented by different strains of L. bulgaricus and S. thermophilus, and by Martin et al (1999) after 30-day storage at 5°C (4.18-4.36). Besides, Damin et al (2006) detected an average lactic acidity in commercial yoghurts (10.1 mg g À1 ) practically coincident to the average value of this work after D7.…”
Section: Post-acidification and Aciditysupporting
confidence: 89%
“…Oliveira et al (2001) observed an increase in firmness from 0.12 to 0.20 N when milk was supplemented with whey and from 0.71 to 0.86 N with milk proteins. The above enforcing effect of storage at 4°C is in agreement with the viscosity increase observed by several authors mainly during the first week of storage (Barrantes et al, 1994;Martin et al, 1999;Zourari et al, 1991). On the other hand, no report is available in the literature about the effect of a complex probiotic cocktail on yoghurt firmness, to which the last part of this work has been addressed.…”
Section: Firmnesssupporting
confidence: 88%
“…In addition, the mass change per time unit (Dm/Dt) versus mass was plotted and linear regression was performed using procedure PROC REG in SAS version 9.1. From the regression equations, the negative reciprocal value of the slope was defined as the flowing time coefficient (FTC) and used as parameter for further studies, i.e., FTC4mm and FTC8mm (Martin et al, 1999). Finally, the efflux time or time necessary to collect 280 g of yoghurt was termed as t280g4mm or t280g8mm.…”
Section: Posthumus Analysesmentioning
confidence: 99%
“…Prior to the measurement, the yoghurts were tempered to 13 C. Thereafter, the funnel was filled and yoghurt was allowed to flow through the orifice. The material exiting the conical part was collected in a beaker whose weight was measured every second by a scale interfaced to a computer Martin, Skokanova, Latrille, Beal, & Corrieu, 1999). The flow curves of weight (g) versus time (s) were fitted to a second-degree polynomial, where the corresponding Table 1 Schematic overview of the experimental design used.…”
Section: Posthumus Analysesmentioning
confidence: 99%